Diversity of traditional and fermented foods of the Seven Sister states of India and their nutritional and nutraceutical potential: a review. Issue 4 (1st October 2016) - Das, Gitishree; Patra, Jayanta Kumar; Singdevsachan, Sameer K.; Gouda, Sushanto; Shin, Han-Seung
ABSTRACT: The Seven Sister states of northeast India are characterized by diverse population with different ethnic backgrounds. Indigenous and fermented foods are an intrinsic part of diet of these ethnic tribes. It is the oldest and most economical methods for development of a diversity of aromas, flavors, and textures as well as for food preservation and biological enrichment by manipulation of different microbial populations. Wild fruits and vegetables have more nutritional value than cultivated fruits and contribute to sustainable food production and security. Fermented products are region-specific and have their own unique substrates and preparation methods. Soybeans, bamboo shoots, and locally available vegetables are commonly fermented by most tribes. Fermented alcoholic beverages prepared in this region are unique and bear deep attachment with socio-cultural lives of local people. These products serve as a source of income to many rural people, who prepare them at home and market them locally. Detailed studies on nutritive and medicinal value of these products can provide valuable information and would prove beneficial in guiding the use of these products on a wider scale. Furthermore, the ethnobotanical field exploration, conservation of indigenous knowledge, and proper documentation of wild edible bio-resources are suggested for sustaining the livelihood of local communities.